Vibrios Commonly Possess Two Chromosomes - Okada, Kazuhisa (American Society for Microbiology, 2005)
The prevalence of the two-chromosome configuration was investigated in 34 species of vibrios and closely related species. Pulsed-field gel electrophoresis of undigested genomic DNA suggested that vibrios commonly have two chromosomes. The size of the large chromosome is predominantly within a narrow range (3.0 to 3.3 Mb), whereas the size of the small chromosome varies considerably among the vibrios (0.8 to 2.4 Mb). This fact suggests that the structure of the small chromosome is more flexible than that of the large chromosome during the evolution of vibrios.